Social Responsibility - A Non-Technological Innovation Process - Mulej, Matjaž; G. Dyck, Robert (Bentham Science Publishers, 2014)
Current global economic crises call for social responsibility to replace neo-liberalistic, one-sided and short-term criteria causing monopolies of global enterprises. Humanity's existence is endangered under the threat of global capitalism, unless the positive concept 'everyone's social responsibility impacts everyone in society' becomes the basis of the new socio-economic order. This concept must be realized together with related concepts of 'interdependence' and 'holism' embodying the principles of accountability, transparency, ethical behavior, and respect for stakeholders–to support the rule of law, international norms, and human rights.Social Responsibility – A non-technological innovation process explores the realm of social responsibility in the context of innovation, business practice and economic crises. Readers can apply related principles to their business practices and enhance their business prospects in a modern environment facing the challenges of socio-economic crises.This volume is intended for graduates and professionals working in government organizations and commercial enterprises, to learn basic concepts about social responsibility and introduce holistic management practices in their daily and professional lives.